Late onset spinal motor neuronopathy is caused by mutation in CHCHD10. Issue 1 (12th December 2014) - Penttilä, Sini; Jokela, Manu; Bouquin, Heidi; Saukkonen, Anna Maija; Toivanen, Jari; Udd, Bjarne
<x xml:space="preserve">Abstract</x> Objective A study was undertaken to identify the responsible gene defect underlying late onset spinal motor neuronopathy (LOSMoN/SMAJ; Online Mendelian Inheritance in Man #615048), an autosomal dominant disease mapped to chromosome 22q11.2. Methods The previous genetic linkage approach by microsatellite haplotyping was continued in new families. A whole genome sequencing was performed to find all possibly pathogenic mutations in the linked area. The detected variations were verified by Sanger sequencing. Results Six new SMAJ families were identified based on the unique founder haplotype. A critical recombination in 1 family restricted the linked area to 727kb between markers SHGC‐106816 and D22S345. In whole genome sequencing a previously unknown mutation c.197G>T p.G66V in CHCHD10 was identified. The mutation was shown to segregate with the disease in 55 patients from 17 families. Interpretation Mutation c.197G>T p.G66V in CHCHD10 is the cause of the lower motor neuron syndrome LOSMoN/SMAJ. During the preparation of this article other mutations were reported to cause frontotemporal dementia–amyotrophic lateral sclerosis syndrome, indicating that the CHCHD10 gene is largely important for the motor and cognitive neuronal systems. ANN NEUROL 2015;77:163–172